2019
DOI: 10.3389/fphar.2018.01536
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nrf2 Modulation to the Mechanism of Action of Analgesic and Anti-inflammatory Drugs in Pre-clinical and Clinical Stages

Abstract: Despite the progress that has occurred in recent years in the development of therapies to treat painful and inflammatory diseases, there is still a need for effective and potent analgesics and anti-inflammatory drugs. It has long been known that several types of antioxidants also possess analgesic and anti-inflammatory properties, indicating a strong relationship between inflammation and oxidative stress. Understanding the underlying mechanisms of action of anti-inflammatory and analgesic drugs, as well as ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 239 publications
(274 reference statements)
2
45
0
1
Order By: Relevance
“…Therefore, the hydroxyl group at B ring seems to be important for ONOO − and superoxide anion scavenging activity and its reasonable that this scavenging activity accounts for flavonoids analgesic and anti-inflammatory activity. Flavonoids also present antioxidant effects by indirect mechanisms through activation of Nrf2 signaling pathway, for example [169]. Chalcones are more potent than other types of flavonoids, where the double bond at C2-C3 position of their structure are particularly important for Nrf2 induction.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%
“…Therefore, the hydroxyl group at B ring seems to be important for ONOO − and superoxide anion scavenging activity and its reasonable that this scavenging activity accounts for flavonoids analgesic and anti-inflammatory activity. Flavonoids also present antioxidant effects by indirect mechanisms through activation of Nrf2 signaling pathway, for example [169]. Chalcones are more potent than other types of flavonoids, where the double bond at C2-C3 position of their structure are particularly important for Nrf2 induction.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%
“…Oxidative stress is also involved in the development and maintenance of neuropathic pain. Nuclear factor erythroid derived-2-related factor 2 (Nrf2) and its downstream pathway, the enzymes heme oxygenase 1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO1), are key to maintaining the homeostasis of organisms [20]. In vivo studies have demonstrated reduced Nrf2 and/or HO-1 levels in the spinal cord of animals with neuropathic pain [12,21] or diabetic neuropathy [22,23,24,25], in which the levels were restored by treatment with several pharmacological modulators of Nrf2 and HO-1 [12,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress causes Nrf2 to dissociate from KEAP1 and, subsequently, to translocate into the nucleus, which results in its binding to ARE and the transcription of downstream target genes [37,38]. We observed nuclear translocation of Nrf2 in the hypoxia group, which explains the upregulation of Prdx6, however, nuclear translocation of Nrf2 was not observed in reperfusion (Fig.…”
Section: Discussionmentioning
confidence: 68%